The Effectiveness of QR Scanner SmartphoneIntegrated Ecosystem-Based Material Modules in Fostering Problem-Solving Skills - Umi Afidah; Baskoro Adi Priyatno; Sutarno Sutarno (Universitas Negeri Malang, 2023)
This study intends to assess how well the integrated teaching module for the QR Scanner in ecological material improves students' problem-solving abilities. In this study, the experimental technique was used with a pretest-posttest control group design. The study's 60 participants were split into two groups: the experimental group and the control group, each of which included 30 participants. The control group did not get any special intervention, whereas the experimental group received it in the form of a QR scanner and HP Integrated Ecosystem-Based Material Modules. Data from the pre- and post-tests of both groups were gathered in order to assess how the intervention affected the groups' problem-solving abilities. Utilizing exams and questionnaires, data was gathered. Paired t tests were used to compare each group's pretest and posttest results in the analysis of the study data. The findings revealed that the experimental group's problem-solving abilities significantly improved (p 0.001), but the control group exhibited no significant difference (p > 0.05). As a result, the integrated teaching module for the QR Scanner in the ecosystem materials was successful in enhancing students' ability to solve problems. The findings of this study have significant ramifications for the design of technology-based learning strategies that will enhance student learning and help them apply concepts in real-world situations.